Decoupling Phytoplankton Biomass—Sediment Phosphorus Interaction Induced by Lower Incident Radiation Mainly Drives the Attenuation of Harmful Algal Blooms in Lake Taihu, China - Ting Pan; Justin Brookes; Chixiao Cui; Boqiang Qin; Kan Ding; Yunlin Zhang; Guangwei Zhu (Water Resources Research, 2025)
Abstract The occurrence, timing and development of algal blooms can be unpredictable under changing climatic conditions. Dramatic fluctuations in algal biomass patterns occurred in Lake Taihu, with a notable surge in blooms magnitude during 2016–2020 followed by a sudden decrease in algal biomass in the period of 2021–2023. The mechanisms underlying this variability are not well understood. Here, a process‐based model was developed to quantify the drivers behind the transition from higher to lower algal biomass patterns. The lower spring photosynthetically active radiation (PAR) during 2021–2023 decreased algal photosynthesis and algal biomass. The subsequent weak phytoplankton–phosphorus (from the sediment) feedback, resulted in decreased phosphate concentration, which in turn further reduced algal biomass. This mechanism underscores the importance of understanding internal nutrient dynamics and the need for stricter measures to reduce external loads to weaken the internal feedback loop between sediment phosphorus release and algal bloom outbreaks, and further to mitigate the effects of climate change on lake ecosystems.